2015
DOI: 10.1063/1.4922527
|View full text |Cite
|
Sign up to set email alerts
|

In operandi observation of dynamic annealing: A case study of boron in germanium nanowire devices

Abstract: Articles you may be interested inInfluence of boron-interstitials clusters on hole mobility degradation in high dose boron-implanted ultrashallow junctions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Furthermore, we compare the growth orientation of Ge NWs at temperatures below and above T e shown in Fig. 5(c), in agreement with the result of Schmidtbauer et al 10 Interestingly, at a low growth temperature, lateral NWs appear along the [1][2][3][4][5][6][7][8][9][10] direction. Scrutinizing through different positions of the NW sample grown at 220 C, we found that the NWs with 30 inclination all possess a long length, thin diameter, and small Au tips, both shown in Figs.…”
Section: (B)supporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we compare the growth orientation of Ge NWs at temperatures below and above T e shown in Fig. 5(c), in agreement with the result of Schmidtbauer et al 10 Interestingly, at a low growth temperature, lateral NWs appear along the [1][2][3][4][5][6][7][8][9][10] direction. Scrutinizing through different positions of the NW sample grown at 220 C, we found that the NWs with 30 inclination all possess a long length, thin diameter, and small Au tips, both shown in Figs.…”
Section: (B)supporting
confidence: 88%
“…Ge nanowires (NWs) have promising electronic properties 1,2 and play an increasingly important role in various applications, such as high speed transistors, [3][4][5] photodetectors, 6,7 and the anode material of high capacity lithium-ion batteries. 8 Conventional Ge NW growth via the Au-assisted vapor-liquid-solid (VLS) process takes place above the Au-Ge eutectic temperature (T e % 361 C).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the case of NWs, observation of enhanced dynamic annealing and absence of extended defects due to the dimensional confinement has been reported in Ge 61 and GaN NWs. 62 Further computational work is required to extend the knowledge of the behavior of the NW arrays under irradiation and to correlate to the electronic properties observed.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, it has been widely reported in the literature that the presence of surfaces/interfaces interact strongly with defects created by collision cascades. , Interfaces can attract, absorb, and annihilate defects. Therefore, nanostructured materials with a high surface-to-volume ratio are expected to exhibit a radiation damage tolerance significantly different from bulk materials. Additionally, in the case of NWs, observation of enhanced dynamic annealing and absence of extended defects due to the dimensional confinement has been reported in Ge and GaN NWs . Further computational work is required to extend the knowledge of the behavior of the NW arrays under irradiation and to correlate to the electronic properties observed.…”
Section: Resultsmentioning
confidence: 99%